Aktueller Stand der neoadjuvanten Therapie bei Weichteilsarkomen - Lehnhardt, Marcus; Schmitt, Thomas; Bischof, Marc; Daigeler, Adrien; Egerer, Gerlinde (Der Chirurg, 2011)
The treatment of soft tissue sarcoma is clinically challenging. Referral to an experienced center with an interdisciplinary team is strongly recommended. Neoadjuvant therapy, including irradiation and chemotherapy, has been applied to improve local control rates, eradicate micrometastases and assess chemosensitivity. However, the role of neoadjuvant therapy remains controversial, especially for systemic therapy, as the only available randomized trial failed to prove a benefit for survival. Nevertheless, on the basis of the current body of literature, neoadjuvant therapy can be considered on an individual basis for patients with high-risk tumors. Whenever possible, patients should be included in a clinical trial.
Gesehen am 10.08.2022